Management System for Waste Handling and Processing at Final Processing Site Pematangsiantar City - Ningsih, Puspa; Awaluddin, Sri Prilmayanti (Golden Ratio of Community Services and Dedication, 2024)
Waste is the remaining waste from human activities in a product or item that is no longer used, but can still be recycled into valuable and useful items. Pematangsiantar City is one of the cities that connects the cross-Sumatra road with its increasingly high population so that it is undeniable that the results of waste generation are increasing and resulting in the condition of landfills (TPA) in Pematangsiantar City becoming overloaded and having an impact on environmental health. The lack of resources and facilities and infrastructure is an obstacle to the smooth running of tasks in terms of waste management in Pematangsiantar City. for this reason, it is hoped that it is necessary to implement a management system for handling and processing waste in landfills that is more effective and efficient with the aim of creating creative human resources (HR) and community participation in clean and healthy environmental awareness. according to the local government logo "LISA" See Trash Take.